Changes in the Quality of Surimi Made from Thornback Ray (Raja Clavata, L. 1758) during Frozen Storage - Turan, Hayrunnisa; Sönmez, G. (Taylor & Francis Ltd, 2007)
Surimi was prepared from the thornback ray (Raja clavata L. 1758) and divided into two groups. The first group was prepared with 4% sorbitol, 4% sucrose and 0.3% sodium tripolyphosphate as a cryoprotectant, while surimi in second group was prepared with 8% sorbitol and 0.3% sodium tripolyphosphate. The frozen surimi samples were stored at -23.8±2°C for 6 months. The total volatile basic nitrogen (8.40 mg/100 g for group A, 6.30 mg/100 g for group B), trimethylamine nitrogen (2.55 mg/100 g for group A, 2.38 mg/100 g for group B), thiobarbituric acid (1.29 mg malondialdehyde/100 g for group A, 1.17 mg malondialdehyde/100 g for group B), and pH values (7.34 for group A, 6.98 for group B) of surimi increased during frozen storage but remained within the acceptable limits. Total psychrophilic aerobic bacteria counts and sensory evaluation points in both groups decreased during frozen storage. The results of this study showed that thornback ray was found to be suitable for surimi production and the surimis were still acceptable at the end of the 6-month storage period.
Keywords: Burgers; Cryoprotectant; Sodium Tripolyphosphate; Sorbitol; Surimi; Thornback Ray